2020
DOI: 10.1016/j.cpc.2019.107087
|View full text |Cite
|
Sign up to set email alerts
|

SIRF: Synergistic Image Reconstruction Framework

Abstract: The combination of positron emission tomography (PET) with magnetic resonance (MR) imaging opens the way to more accurate diagnosis and improved patient management. At present, the data acquired by PET and MR scanners are essentially processed separately, and the search for ways to improve accuracy of the tomographic reconstruction via synergy of the two imaging techniques is an active area of research. The aim of the collaborative computational project on PET and MR (CCP-PETMR), supported by the UK engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…The draft PET BIDS standard does not yet extend to listmode data [37], so we applied our BIDS-like standard [21] to ensure that it is consistent with the Interoperable principle of the FAIR philosophy. We [21] have previously demonstrated that listmode fPET data can be accurately reconstructed using open source methods STIR [38] and SIRF [39], confirming the Monash DaCRA fPET-fMRI dataset is also consistent with the Reusable principle of the FAIR philosophy.…”
Section: Concluding Remarks and Re-use Potentialsupporting
confidence: 61%
“…The draft PET BIDS standard does not yet extend to listmode data [37], so we applied our BIDS-like standard [21] to ensure that it is consistent with the Interoperable principle of the FAIR philosophy. We [21] have previously demonstrated that listmode fPET data can be accurately reconstructed using open source methods STIR [38] and SIRF [39], confirming the Monash DaCRA fPET-fMRI dataset is also consistent with the Reusable principle of the FAIR philosophy.…”
Section: Concluding Remarks and Re-use Potentialsupporting
confidence: 61%
“…A practical difficulty with synergistic methods, especially in multi-modality imaging, is the need for software that can handle large amounts of data, is capable of accurately computing the system models (2.3), and ideally allows easy experimentation with novel algorithms. It is therefore often necessary to combine several software packages, ideally via an overarching framework [132] or by writing interfaces to other packages such that they can be used in an optimization library such as [133][134][135].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…We used Software for Tomographic Image Reconstruction (STIR) (v.4.0) [38], [39] for the reconstruction of the simulated data, using TOF Listmode Maximum Likelihood-Expectation Maximisation (LM-MLEM) as it is the most robust option and is guaranteed to converge to a solution [40]. The validation of the TOF reconstruction with Gaussian [40]- [42] and non-Gaussian [43] kernels has been presented in detail previously.…”
Section: Image Reconstruction Toolkitmentioning
confidence: 99%